Ḥikāyat abī al-qas̄im : a literary banquet - Selove, Emily (Edinburgh studies in classical Arabic literature., 2016)
Re-introduces a poorly understood, provocative and unusual work to a new audience. Hikayat Abi al-Qasim, probably written in the 11th century by the otherwise unknown al-Azdi, tells the story of a gate-crasher from Baghdad named Abu l-Qasim, who shows up uninvited at a party in Isfahan. Dressed as a holy man and reciting religious poetry, he soon relaxes his demeanour, and, growing intoxicated on wine, insults the other dinner guests and their Iranian hometown. Widely hailed as a narrative unique in the history of Arabic literature, Hikayah also reflects a much larger tradition of banquet texts. Painting a picture of a party-crasher who is at once a holy man and a rogue, he is a figure familiar to those who have studied the ancient cynic tradition or other portrayals of wise fools, tricksters and saints in literatures from the Mediterranean and beyond. This study therefore compares Hikayah, a mysterious text surviving in a single manuscript, to other comical banquet texts and party-crashing characters, both from contemporary Arabic literature and from Ancient Greece and Rome. Key Features. Uses a new method of reading medieval Arabic literature in dialogue with Classical literature, especially from Ancient Greece and Rome Looks at pre-modern notions of representation and description in literature Includes an abridged translation of Hikayat, giving the reader a taste of its both amusing and shocking content